Effect of Ca on the performance of Mg-Mn sacrificial anodes by electrochemical corrosion techniques - Shaiful Rizam, Shamsudin; C. I., Mahdi; Mohd Nazree, Derman; A. M. H., Firdaus; A. R., Daud; T., Loshniban (Universiti Malaysia Perlis, 2010)
The 25th Regional Conference of Solid State Science and Technology 2009 (RCSSST 2009) jointly organized by Universiti Malaysia Perlis (UniMAP) and Malaysian Solid State Science & Technology Society (MASS), 21st - 23rd December 2009 at Bayview Beach Resort, Ferringhi in the Pearl of the Orient, Penang.